The Effectiveness of Group Counseling with Self-Management and Cognitive Restructuring Techniques to Reduce Students’ Aggression (Universitas Negeri Semarang, 2020)
This study aimed at analyzing the effectiveness of group counseling with self-management and cognitive restructuring techniques to reduce the aggression of the students of SMK LPI Semarang. The study employed randomized pretest-posttest comparison group. There were 18 students selected as experimental subjects, and placed into three groups (each were six students) randomly. It had no control group, but comparison group with the intervention of the combination of two techniques. The data from the groups were collected using aggression questionnaire scale. The results of wilcoxon test showed that self-management technique was effective to reduce students’ aggression (Z = 2.201, p < 0.05, while cognitive restructuring technique also effectively reduced aggression (Z = 2.207, p < 0.05), and the combination of self-management and cognitive restructuring techniques effectively reduced students' aggression (Z = 2.201, p < 0.05). These findings confirm that the group counseling with self-management and cognitive restructuring techniques is effective to reduce students’ aggression.